2021
DOI: 10.1002/anie.202110433
|View full text |Cite
|
Sign up to set email alerts
|

Phosphorus Induced Electron Localization of Single Iron Sites for Boosted CO2 Electroreduction Reaction

Abstract: Electrochemical reduction of carbon dioxide (CO2) into chemicals and fuels has recently attracted much interest, but normally suffers from a high overpotential and low selectivity. In this work, single P atoms were introduced into a N‐doped carbon supported single Fe atom catalyst (Fe‐SAC/NPC) mainly in the form of P−C bonds for CO2 electroreduction to CO in an aqueous solution. This catalyst exhibited a CO Faradaic efficiency of ≈97 % at a low overpotential of 320 mV, and a Tafel slope of only 59 mV dec−1, co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
134
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 238 publications
(142 citation statements)
references
References 67 publications
2
134
0
Order By: Relevance
“…Previous work showed that most carbon-supported SACs with abundant nitrogen-doped are stable activated single-metal ions to form the homogeneous microcosmic structure of M-N x -C y . The universal methods for synthesizing carbon-supported SACs include molecular skeleton encapsulation, [34][35][36][37][38] impregnation and pyrolysis, [39][40][41] coordination regulation, [42][43][44] and thermal dispersion.…”
Section: Carbon-supported Sacsmentioning
confidence: 99%
“…Previous work showed that most carbon-supported SACs with abundant nitrogen-doped are stable activated single-metal ions to form the homogeneous microcosmic structure of M-N x -C y . The universal methods for synthesizing carbon-supported SACs include molecular skeleton encapsulation, [34][35][36][37][38] impregnation and pyrolysis, [39][40][41] coordination regulation, [42][43][44] and thermal dispersion.…”
Section: Carbon-supported Sacsmentioning
confidence: 99%
“…Reasonable structures not only increase the exposure active site avoid aggregation, but also can regulate the interaction between the adsorbate and the catalyst, [17][18][19] which is why single-atom catalysts have been widely used in the field of carbon dioxide reduction in recent years. [20,21] Similar to this idea, self-supporting nanomaterials exhibit a three-dimensional (3D) structure, porosity and high specific surface area compared to bulk materials, which is ideal candidates for electrocatalytic reaction. [22] Various nanomaterials based on self-supporting have been used for CO 2 RR catalysts for decades, such as nanowires, [23] nanorods, [24] nanosheets, [25] nanotubes, [26] aerogels, [27,28] and graphene.…”
Section: Introductionmentioning
confidence: 99%
“…It is equivalent to adjusting the catalyst surface‘s geometry by designing the morphology and components rationally and reducing the size. Reasonable structures not only increase the exposure active site avoid aggregation, but also can regulate the interaction between the adsorbate and the catalyst, [17–19] which is why single‐atom catalysts have been widely used in the field of carbon dioxide reduction in recent years [20,21] . Similar to this idea, self‐supporting nanomaterials exhibit a three‐dimensional (3D) structure, porosity and high specific surface area compared to bulk materials, which is ideal candidates for electrocatalytic reaction [22] .…”
Section: Introductionmentioning
confidence: 99%
“…Among the wide variety of proposed technologies, electrochemical energy transformation technologies, such as water splitting, CO 2 reduction, fuel cells and metal-air batteries, are considered to be among the most effective substitutes for traditional fossil energy [10][11][12][13][14][15][16][17][18] . Previously reported electrocatalysts have shown high activity and superior stability, most of which are composed of precious transition-metal nanoparticles (NPs), such as Pt/C, RuO 2 and IrO 2 [19][20][21][22][23][24] . However, these precious metalbased catalysts have high costs and scarce reserves, which severely restrict their large-scale application [25][26][27][28][29][30][31] .…”
Section: Introductionmentioning
confidence: 99%